Benchmarking sample preparation/digestion protocols reveals tube‐gel being a fast and repeatable method for quantitative proteomics. Issue 23 (December 2016) - Muller, Leslie; Fornecker, Luc; Van Dorsselaer, Alain; Cianférani, Sarah; Carapito, Christine
Abstract : Sample preparation, typically by in‐solution or in‐gel approaches, has a strong influence on the accuracy and robustness of quantitative proteomics workflows. The major benefit of in‐gel procedures is their compatibility with detergents (such as SDS) for protein solubilization. However, SDS‐PAGE is a time‐consuming approach. Tube‐gel (TG) preparation circumvents this drawback as it involves directly trapping the sample in a polyacrylamide gel matrix without electrophoresis. We report here the first global label‐free quantitative comparison between TG, stacking gel (SG), and basic liquid digestion (LD). A series of UPS1 standard mixtures (at 0.5, 1, 2.5, 5, 10, and 25 fmol) were spiked in a complex yeast lysate background. TG preparation allowed more yeast proteins to be identified than did the SG and LD approaches, with mean numbers of 1979, 1788, and 1323 proteins identified, respectively. Furthermore, the TG method proved equivalent to SG and superior to LD in terms of the repeatability of the subsequent experiments, with mean CV for yeast protein label‐free quantifications of 7, 9, and 10%. Finally, known variant UPS1 proteins were successfully detected in the TG‐prepared sample within a complex background with high sensitivity. All the data from this study are accessible on ProteomeXchange (PXD003841).